Kritik Jawa atas Teori Hubungan Internasional Barat - Yusli Effendi; Dion Maulana Prasetya (Jurnal Transformasi Global, 2016)
International Politics studies have been dominated by Western discourse. The domination has also been affected Indonesian academic circles, which is also having so many difficulties to escape themselves from Western perspectives, especially from American School. Consequently, IR scholars usually analize Indonesia behaviours by using Western perspectives which have no roots in Nusantara history. This article will try to do the hung up ‘homework’, by doing an alternative discourse of power in International Politics studies from Javanese perspectives, by using Historical Sociology method. This article argues that the Javanese concept of power is ontologically and epistemologically different from the Western concept of power. Ontologically, in Javanese thoughts, anarchy along with its derivatives, balance of power, does not exist; epistemologically, power is concrete, homogenous, and beyond morality. On the other hand, in Western thoughts, international anarchy is the state of nature, and power depends on material accumulation and its utilization. The differences both on epistemological and ontological level have logical consequences to the foreign policy characteristics of the Javanese leaders.Keywords: Power, Absorption, Historical Sociology, Non-Western IRT